Detection of α-synuclein oligomers in red blood cells as a potential biomarker of Parkinson's disease. (10th July 2015) - Wang, Xuemei; Yu, Shun; Li, Fangfei; Feng, Tao
Highlights: We showed that the ratio of α-syn oligomer/total RBC protein was higher in PD patients than in controls. There was no correlation between RBC α-syn oligomer levels and age at onset or UPDRS score in PD patients. The present results suggest that the RBC α-syn oligomer/total protein ratio can be a potential diagnostic biomarker for PD. Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by intracellular α-synuclein (α-syn) deposition. Alterations in α-syn levels in cerebrospinal fluid (CSF) and plasma of PD patients have been thought to be potential PD biomarkers; however, contamination arising from hemolysis often influences the accuracy of detecting α-syn levels in the CSF and plasma. In this study, α-syn oligomer levels in red blood cells (RBCs) obtained from 100 PD patients, 22 MSA patients, and 102 control subjects were measured by enzyme-linked immunosorbent assay. We showed that the ratio of α-syn oligomer/total RBC protein was higher in PD patients than in controls (29.0 ± 19.8 ng/mg vs. 15.4 ± 7.4 ng/mg, P  < 0.001). The area under the receiver operating characteristic curve (AUC) indicated a sensitivity of 79.0%, specificity of 64.7% and a positive predictive value of 68.7%, with an AUC of 0.76 for increased α-syn oligomer/total RBC protein ratio. However, there was no correlation between RBC α-syn oligomer levels and age at onset, disease duration, age, UPDRS motor scale score or progression of motor degeneration in PD patients. The ratio of RBC α-syn oligomer/total protein was also higher in MSA patients than in controls (22.9 ± 13.9 ng/mg vs. 15.4 ± 7.4 ng/mg, P  < 0.001). However, no significant difference was found for α-syn oligomer/total protein ratio between PD and MSA (29.0 ± 19.8 ng/mg vs. 22.9 ± 13.9 ng/mg, P  > 0.05). The present results suggest that the RBC α-syn oligomer/total protein ratio can be a potential diagnostic biomarker for PD.